Study guides

☆☆

Q: How do you solve 2x squared plus x plus 2 equals 0 by completing the square?

Write your answer...

Submit

Still have questions?

Related questions

i want to solve few questions of completing square method can u give me some questions on it

If x squared -10 = 0 then x = the square root of 10

Square root both sides and then x = 4

Solve this problem -x squared -40x- 80 =0

5.

If x squared equals n, then x is the square root of n.

This question cannot be answered. You will have to give me the number to the square root. * * * * * a = ±sqrt(c^2 - b^2)

root 7

x = 2

h = +11 and/or -11

If r-squared = theta then r = Â±sqrt(theta)

This quadratic equation has no solutions because the discriminant is less than zero.

x2=-81take the square root of both sidessince 81 is negative you need to take 81 times i when i=-1 then solve as the square root of 81. your answer is x=9i

Yes and x = 2+square root of 6 or x = 2-square root of 6

I couldn't answer the question because the question is not proper to slove. I just want you to follow the related link that explains how to solve the equation by completing the square.

Completing the square is a method used to solve a quadratic function. This is a handy method when there are two instances of the same variable in the function.

The related link "Purple Math" has an in depth explanation.

Please do not remove this question from Inappropriate or split any alts from it. Thanks!

Divide all terms by 3 so:- x2-4x = 5 Completing the square:- (x-2)2 = 9 x-2 = -/+3 x = -1 or x = 5

Solve using the quadratic formula

-2y square exp power -2x-1

x^2 = 64 x = +,- square root of 64 = +,- 8. Thus, x = -8 or x = 8

m2 - 8m = 0Factor the expression on the left:m (m - 8) = 0If either factor is zero, then the two sides are equal:m - 8 = 0m = 8m = 0

If you aren't dealing with algebra, such as x2+3x+21, then completing the square wont be able to solve the porblem, however if you are using algebra, and you cannot factorise, then completing the square will always work

(x-5)(x+3)